2004
DOI: 10.1111/j.1432-1033.2004.04194.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of Bacillus subtilis type II isopentenyl diphosphate isomerase, and phylogenetic distribution of isoprenoid biosynthesis pathways

Abstract: An open reading frame (Acc. no. P50740) on the Bacillus subtilis chromosome extending from bp 184 997-186 043 with similarity to the idi-2 gene of Streptomyces sp. CL190 specifying type II isopentenyl diphosphate isomerase was expressed in a recombinant Escherichia coli strain. The recombinant protein with a subunit mass of 39 kDa was purified to apparent homogeneity by column chromatography. The protein was shown to catalyse the conversion of dimethylallyl diphosphate into isopentenyl diphosphate and vice ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
83
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 53 publications
2
83
0
1
Order By: Relevance
“…These studies proposed that the MVA pathway is germane to archaea (where it is required for the production of membrane ether-linked isoprenoid lipids) whereas the MEP pathway is the ancestral route in bacteria, serving for the production of precursors for quinones, carotenoids, and membrane stabilizers such as hopanoids. Although the majority of bacteria exclusively use the MEP pathway for IPP and DMAPP biosynthesis, there are some exceptions (20)(21)(22). For example, several species of parasitic Rickettsia and Mycoplasma bacteria have no genes encoding enzymes of the MVA or the MEP pathway, probably because they obtain their isoprenoids from host cells.…”
Section: Discussionmentioning
confidence: 99%
“…These studies proposed that the MVA pathway is germane to archaea (where it is required for the production of membrane ether-linked isoprenoid lipids) whereas the MEP pathway is the ancestral route in bacteria, serving for the production of precursors for quinones, carotenoids, and membrane stabilizers such as hopanoids. Although the majority of bacteria exclusively use the MEP pathway for IPP and DMAPP biosynthesis, there are some exceptions (20)(21)(22). For example, several species of parasitic Rickettsia and Mycoplasma bacteria have no genes encoding enzymes of the MVA or the MEP pathway, probably because they obtain their isoprenoids from host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Reduction of the cofactor with NADPH or dithionite was required to generate an active enzyme·reduced flavin complex (15;16;27;29). Laupitz and coworkers (18) reported that B. subtilis type II isomerase purified from an recombinant E. coli strain under anaerobic conditions was active without addition of NADPH to the assay buffer. It is curious to note, that they also reported that added FMN was required for activity in the anaerobic assay and that FMN was not reduced by NADPH in the presence of enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The spectral changes for the reduced, enzyme-bound 1-deaza and 5-deazaFMN analogues in the presence of IPP are also consistent with the accumulation of their neutral reduced forms. The protonation in the N1/C1-C2═O2â€Č region of all three coenzymes may be mediated by Lys186 or His149 (S. aureus numbering), both of which are absolutely conserved among IDI-2 enzymes (15)(16)(17)20). Previously, we have suggested that IPP binding may induce a conformational change that results in a K m value for reduced FMN (200 nM) that is 70-fold lower than the K d (14 ”M) value for binding of the reduced FMN to IDI-2 in the absence of IPP (21).…”
Section: Discussionmentioning
confidence: 99%
“…After shimming and initial peak integration, enzyme was added to the NMR tube, and the appearance of the (Z)-methyl proton resonance of DMAPP (ÎŽ = 1.66 ppm) (13,15,28) was followed over 120 min using a Varian Unity 500 MHz NMR spectrometer. The spectra at each individual time point were acquired over a 220 s interval, and a 180 s delay time was used between successive data acquisition periods.…”
Section: In Situ Nmr Assay For Initial Velocity Determinationmentioning
confidence: 99%
See 1 more Smart Citation